2016
DOI: 10.1016/j.phrs.2016.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of soluble guanylyl cyclase redox state by hydrogen sulfide

Abstract: Soluble guanylate cyclase (sGC) is a receptor for nitric oxide (NO). Binding of NO to ferrous (Fe2+) heme increases its catalytic activity, leading to the production of cGMP from GTP. Hydrogen sulfide (H2S) is a signalling molecule that exerts both direct and indirect anti-oxidant effects. In the present, study we aimed to determine whether H2S could regulate sGC redox state and affect its responsiveness to NO-releasing agents and sGC activators. Using cultured rat aortic smooth muscle cells, we observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 57 publications
(74 reference statements)
1
60
0
2
Order By: Relevance
“…Similarly, CORM-2-mediated gastroprotection against aspirin-or ethanol-induced injury was reduced by co-treatment with ODQ or indomethacin respectively (Gomes et al, 2010;Magierowska et al, 2015;Magierowski et al, 2016a). Bucci et al (2012) and Zhou et al (2016) also demonstrated that H 2 S can stimulate NOmediated sGC activity, and therefore, H 2 S-mediated vasorelaxation has been considered to be cGMP-dependent, similar to the effect of CO. Moreover, H 2 S released from diallyl sulfide decreased nitrite production in intestinal epithelial cells (Fasolino et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, CORM-2-mediated gastroprotection against aspirin-or ethanol-induced injury was reduced by co-treatment with ODQ or indomethacin respectively (Gomes et al, 2010;Magierowska et al, 2015;Magierowski et al, 2016a). Bucci et al (2012) and Zhou et al (2016) also demonstrated that H 2 S can stimulate NOmediated sGC activity, and therefore, H 2 S-mediated vasorelaxation has been considered to be cGMP-dependent, similar to the effect of CO. Moreover, H 2 S released from diallyl sulfide decreased nitrite production in intestinal epithelial cells (Fasolino et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…() and Zhou et al . () also demonstrated that H 2 S can stimulate NO‐mediated sGC activity, and therefore, H 2 S‐mediated vasorelaxation has been considered to be cGMP‐dependent, similar to the effect of CO. Moreover, H 2 S released from diallyl sulfide decreased nitrite production in intestinal epithelial cells (Fasolino et al ., ).…”
Section: Discussionmentioning
confidence: 94%
“…In addition, Cyb5R3 may contribute to the maturation of sGC itself by participating in the heme insertion and reduction process and possibly protein folding 56 . Lastly, it has been reported that H 2 S can reduce oxidized sGC 57 ; however, it is unknown whether Cyb5R3 impacts this pathway. Future work dedicated to understanding the broad impact of Cyb5R3 on sGC-cGMP is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of H 2 S to up regulate cGMP levels is, at least in part, due to the direct inhibition of PDE activity by H 2 S [70, 88] (Fig.2). Moreover, H 2 S converts sGC to its ferrous, NO-responsive form and further increases cGMP [90]. Furthermore, H 2 S production also activates the phosphoinositide 3-kinase (PI3K)/serine/threonine kinase (Akt) pathway, leading to endothelial nitric oxide synthase (eNOS) phosphorylation and eNOS activation [70, 72, 91].…”
Section: H2s Signaling In Angiogenesis: Downstream Mediatorsmentioning
confidence: 99%